Relationship between Family Support and Attitudes Towards the Independence of Post-Stroke Patients in Performing Activity Of Daily Living (ADL) At the Neurology Polyclinic of RSUP Dr.M.Djamil Padang In 2017 - Alisa, Fitria (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Stroke is the first cause of serious disability in the world. In general, the condition of patients post-stroke experience interference on the part of the lower or upper extremities and difficulty in speaking. So patients post stroke should routinely perform the activity of daily living to increase self-sufficiency in post-stroke patients. The purpose of this research is to know the relationship of family support and attitude toward self-sufficiency in post-stroke patients in performing the activity of daily living in nerve polyclinic at RSUP Dr. M. Djamil Padang year 2017. This type of research is descriptive analytic, cross-sectional design research. The population in this research the entire post-stroke patients who visited the nerve polyclinic at RSUP Dr. M. Djamil Padang totaled 134 people. The number of samples 45 people taken with accidental sampling techniques. the data analyzed in Univariate and bivariate use test chi-square with a confidence level of 95% with a value of Î± = 0.05. The results showed more than half 75.6% (34) in post-stroke patients have good family support, more than halfÂ 73.3% (33) of the patient's post-stroke has a negative attitude. The results of statistical tests obtained P value (â‰¥ 0.05) mean no relation of family support with independence post-stroke patients in performing the activity of daily living and the P value (< 0.05) means that there is a relation of attitude with independence post-stroke patients in performing the activity of daily living in nerve polyclinic atÂ RSUP Dr. M. Djamil Padang It can be concluded that patients in post-stroke that have good family support and negative attitude at minimum need some help in performing ADL. It is therefore expected to nurse or a health team to provide encouragement and explanation of the importance of doing an exercise routine to achieve independence of the ADL.